Energy transfer in zinc porphyrin-phthalocyanine heterotrimer and heterononamer studied by fluorescence resonance energy transfer (FRET) - Durmuş, Mahmut; Chen, J. Y.; Zhao, Z. X.; Nyokong, T. (Pergamon-Elsevier Science Ltd, 2008)
Two or eight zinc triphenyl porphyrins were conjugated with Zn-phthalocyanine or H-2-phthalocyanine to form ZnPc-(ZnTPP)(2), ZnPc-(ZnTPP)(8), H2Pc-(ZnTPP)(2) and H2Pc-(ZnTPP)(8). Energy transfers from the porphyrin moiety to phthalocyanine part were quantitatively studied with the modality of fluorescence resonance energy transfer (FRET). By measuring the fluorescence increment from the phthalocyanine moiety and the decrease from porphyrin part under selective excitation at the B band of the porphyrin part in those conjugated compounds and their equimolar mixture of compositions, energy transfer efficiencies were estimated to be 90% for H2Pc-(ZnTPP)(8) and ZnPc-(ZnTPP)(8), and 60%, 30% for ZnPc-(ZnTPP)(2) and H2Pc-(ZnTPP)(2), respectively. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: zinc porphyrin; zinc phthalocyanine; fluorescence; energy transfer